Povilas Višinskis Šiauliai County Public Library Employees’ Ego-Documents: Memoirs and Diaries of Deportations - Baškienė, Audronė (Bibliotheca Lituana, 2018)
[full article and abstract in Lithuanian; abstract in English]The article examines the memoirs and diaries written by the library employees who were born in exile and survived it. The ego-documents are kept in the library Manuscript Fund. The librarian Nijolia Kasparavičienė has assembled them into the local lore work „Long Years of Exile (1991). The collection consists of written personal memoirs of ten library employees, former political prisoners and deportees, who appended their ego-documents with photographs and documents. In 1991–1992 the former deportees organized expeditions to Kazakhstan and Siberia. In such a way two diaries titled as The Second Expedition to Carlag (1991, August 9–19) and „The Siberia reaches“ (1992, August 4–22) were formed. The impressions of the expeditions were written down in a diary form by the librarian, the deportees’ daughter Nijolia Kasparavičienė. The basic idea of the memoirs suggests that one’s own destiny is marked by the fate of the native country Lithuania. The diary recorded the visited places, the encountered people who had expressed their attitude about the past and the prediction about independent Lithuania‘s future. The author of the diaries did not use any literature or historical material. The diaries recorded only personal experiences, data and events.